The human medial temporal lobe represents memory items in their ordinal position in both declarative and motor memory domains - Temudo, Ainsley; Dolfen, Nina; King, Bradley R.; Albouy, Genevieve (PLOS Biology, 2025)
Different memory domains can recruit similar brain areas, but it is not known if the functional role of these overlapping regions is shared or domain-specific. This neuroimaging study shows that the function of the hippocampus to preserve the order of sequential behaviors is shared across memory domains.